Shaping the undergraduate pain management curriculum in prehospital emergency care education: toward a curriculum and competency framework for South Africa - Matthews, Ryan (Division of Emergency Medicine, 2026)
Introduction: Managing patients' pain is a common necessity in Prehospital Emergency Care. Research evidence suggests that pain and nociception are not optimally managed by Emergency Medical Services. One reason for this suboptimal management may be education that is misaligned with clinical and contextual needs. The knowledge gap is that Prehospital Emergency Care has not systematically developed evidence-informed competencies for pain management. Aim: This research aimed to develop a competency framework and provide recommendations for curriculum implementation to shape and guide the design of contextually relevant pain management curricula in South African Prehospital Emergency Care education. Methods: Subsequent to a narrative analysis of pain discourse, the research employed a scoping review of therapies to identify quality and therapeutic possibilities as evidentiary basis for competencies. Semi-structured interviews with educators explored contemporary education practice and documented knowledge broker perspectives on educational needs through thematic analysis. The initial competency framework was inductively derived from the above analyses. Content analysis of contemporary curriculum documents mapped key graduate attributes and identified deficient or absent learning intentions and related success criteria. An expert consensus panel provided critical input into the draft competency framework and made recommendations toward curriculum implementation. Findings: Contemporary curricula are fragmented and misaligned with pain assessment and management needs. Seven competency domains (given expression to by specific competency statements) should guide curriculum development: 1. Clinical Pain Praxis, 2. Foundational Sciences, 3. Practitioner Wellness and Safety, 4. Communication and Collaboration, 5. Duty of Care and Predisposition for Caring, 6. Ethical Practice, and 7. Scholarship. The expert panel made ten recommendations for implementing the framework in curricula, including the use of a ‘spiral' curriculum, focusing on the multidimensional nature of pain, and building relationships with clinical mentors. Conclusion: The novel output of the study is an evidence-based competency framework, compatible with micro credentialing or for local adaptation and progressive inclusion into emergency care curricula. This framework redresses the practice difficulties experienced by key stakeholders and enables higher education institutions and professional regulators to comprehensively and inclusively guide education providers in the noble pursuit of quality and equity in pain assessment and management across the lifespan and across clinical acuity and pain causation.